2021
DOI: 10.3389/fpsyg.2021.764030
|View full text |Cite
|
Sign up to set email alerts
|

The Impostor Phenomenon: Toward a Better Understanding of the Nomological Network and Gender Differences

Abstract: The impostor phenomenon (IP) refers to the tendency to perceive oneself as intellectually incompetent and to attribute one’s own success to effort-related or external factors, such as fortunate circumstances. The present study (N=209) aimed to contribute to open questions regarding gender differences in the IP and the nomological network of the IP. The results show that the consistently found key correlates of the IP, that is, lower self-esteem and higher neuroticism, could also play a role in explaining why w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
4
0
3
Order By: Relevance
“…However, given that the impostor phenomenon has not been defined by the Diagnostic and Statistical Manual of Mental Disorders, the sensitivity and specificity of this scale have not been evaluated, and the high levels of impostor phenomenon captured herein could also be reflective of other character traits, such as perfectionism, which have been shown to be associated with the impostor phenomenon across the psychology literature. 23,[46][47][48][49] Despite these limitations, this study is the first to define the incidence and predictors of the impostor phenomenon in plastic surgery residents and faculty. Our ultimate goal for these findings is to inform future national studies assessing the effects of impostor phenomenon on burnout and career advancement in academic plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that the impostor phenomenon has not been defined by the Diagnostic and Statistical Manual of Mental Disorders, the sensitivity and specificity of this scale have not been evaluated, and the high levels of impostor phenomenon captured herein could also be reflective of other character traits, such as perfectionism, which have been shown to be associated with the impostor phenomenon across the psychology literature. 23,[46][47][48][49] Despite these limitations, this study is the first to define the incidence and predictors of the impostor phenomenon in plastic surgery residents and faculty. Our ultimate goal for these findings is to inform future national studies assessing the effects of impostor phenomenon on burnout and career advancement in academic plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not find gender-specific differences in the IP, and there was no statistically significant difference between males and females suffering from the IP. A study of 209 individuals found that women report higher impostor feelings than men in many studies, possibly due to lower self-esteem and higher neuroticism [12]. A study found that male impostors react more negatively to performance cues, such as negative feedback and perceived accountability, than female impostors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the existence of an indirect effect is supported when the CI does not include zero ( MacKinnon et al, 2007 ). In all analyses, we controlled for gender as a covariate to account for potential gender differences as described in the literature (e.g., Badawy et al, 2018 ; Fleischhauer et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The IP relates negatively to students’ academic self-evaluations and achievement orientations (e.g., King and Cooley, 1995 ; Parkman, 2016 ; Cisco, 2020 ) and goes along with lower self-efficacy, self-esteem, growth mindset, and performance-efficacy (e.g., Cozzarelli and Major, 1990 ; Chrisman et al, 1995 ; Brauer and Wolf, 2016 ; Bravata et al, 2020 ; Fleischhauer et al, 2021 ). Further, the IP shows positive associations with students’ anxiety (i.e., generalized and test anxiety; e.g., Clance, 1985 ; Chrisman et al, 1995 ; Thompson et al, 1998 ), depressiveness, student status stress, psychological distress, and learned helplessness (e.g., Clance, 1985 ; Chrisman et al, 1995 ; Thompson et al, 1998 ; Brauer and Wolf, 2016 ; Ibrahim et al, 2022 ; see also Sakulku and Alexander, 2011 ).…”
Section: Introductionmentioning
confidence: 99%